2021
DOI: 10.1093/ofid/ofab076
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Chronic Liver Enzyme Elevation in Persons With HIV Without Hepatitis B or C Coinfection in the Combination Antiretroviral Therapy Era

Abstract: Background As morbidity due to viral co-infections declines among HIV-infected persons, changes in liver related morbidity are anticipated. We examined data from the US Military HIV Natural History Study (NHS), a cohort of military beneficiaries, to evaluate incidence and risk factors associated with chronic liver enzyme elevation (cLEE) in HIV mono-infected patients in the combination antiretroviral therapy (cART) era. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
1
4
0
2
Order By: Relevance
“…Multiple factors may contribute to increase the risk of liver disease in the context of human immunodeficiency virus (HIV) infection, including infectious and noninfectious comorbidities, metabolic disorders, and the possible direct effects of HIV infection and antiretroviral therapy (ART). [ 1 , 2 , 3 , 4 ] In a systematic review of 10 cross‐sectional studies of primarily men living with HIV in North America, Western Europe, China, and Japan, 35% met the definition of nonalcoholic fatty liver disease (NAFLD) based on imaging or liver histology. [ 1 ] Metabolic disorders and high CD4 cell counts were associated with NAFLD, whereas duration of HIV infection, duration of ART, HIV RNA load, and nadir CD4 cell counts were not.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors may contribute to increase the risk of liver disease in the context of human immunodeficiency virus (HIV) infection, including infectious and noninfectious comorbidities, metabolic disorders, and the possible direct effects of HIV infection and antiretroviral therapy (ART). [ 1 , 2 , 3 , 4 ] In a systematic review of 10 cross‐sectional studies of primarily men living with HIV in North America, Western Europe, China, and Japan, 35% met the definition of nonalcoholic fatty liver disease (NAFLD) based on imaging or liver histology. [ 1 ] Metabolic disorders and high CD4 cell counts were associated with NAFLD, whereas duration of HIV infection, duration of ART, HIV RNA load, and nadir CD4 cell counts were not.…”
Section: Introductionmentioning
confidence: 99%
“…A infecção pelo vírus HIV não tratada e uma elevada carga viral podem ocasionar um aumento nos níveis das transaminases hepáticas, devido à ação direta do vírus nas células hepáticas e ao processo inflamatório sistêmico. Em muitos casos a atividade anormal das transaminases ocorre de forma assintomática e é uma consequência da infecção pelo HIV, sendo necessário tratar a infecção pelo HIV, objetivando reduzir a carga viral e normalizar os índices das transaminases (Kim et al, 2008;Wood et al, 2021). Outros estudos mostraram correlação entre a carga viral do HIV e o grau de elevação das enzimas hepáticas, sendo observado uma redução dos níveis das transaminases à medida que a viremia diminui (Mata-Marín et al 2009;Dusingize et al 2015;Alghamdi et al 2016).…”
Section: Resultsunclassified
“…Estudos realizados por outros autores mostram que a elevação discreta nas enzimas geralmente é transitória e não necessita interrupção no tratamento. No entanto, se houver toxicidade grave (elevação > 5 vezes o limite superior da normalidade) ou se a pessoa apresentar sintomas graves, sugere-se trocar o tratamento (Martins et al, 2020;Wood et al, 2021). Em nosso estudo, o aumento da FAL foi discreto e permaneceu dentro do valor de referência (65 a 300 UI/L), sem indicar necessidade em mudar esquema de TARV.…”
Section: Resultsunclassified
“…This suggests that elevations in one liver enzyme may be accompanied by elevations in the other, reflecting potential liver injury or inflammation. However, Wood et al 2021 reported that long-term use of INSTI-based ART reduces liver enzyme elevation by half compared to those on NNRTI [23]. This observed difference may, however, be due to differences in race, ethnicity, and study design.…”
Section: Discussionmentioning
confidence: 99%